Colloidal Ni–Co–Sn nanoparticles as efficient electrocatalysts for the methanol oxidation reaction. Issue 45 (5th November 2018) - Li, Junshan; Luo, Zhishan; He, Feng; Zuo, Yong; Zhang, Chaoqi; Liu, Junfeng; Yu, Xiaoting; Du, Ruifeng; Zhang, Ting; Infante-Carrió, Maria F.; Tang, Pengyi; Arbiol, Jordi; et al.
Abstract : Ni–Co–Sn alloys show improved performance toward the methanol oxidation reaction in alkaline media. Abstract : The deployment of direct methanol fuel cells requires engineering cost-effective and durable electrocatalysts for the methanol oxidation reaction (MOR). As an alternative to noble metals, Ni-based alloys have shown excellent performance and good stability toward the MOR. Herein, we present a series of Ni3− x Co x Sn2 colloidal nanoparticles (NPs) with composition tuned over the entire Ni/Co range (0 ≤ x ≤ 3). We demonstrate electrodes based on these ternary NPs to provide improved catalytic performance toward the MOR in an alkaline medium when compared with binary Ni3 Sn2 NPs. A preliminary composition optimization resulted in Ni2.5 Co0.5 Sn2 NP-based electrodes exhibiting extraordinary mass current densities, up to 1050 mA mg −1, at 0.6 V vs. Hg/HgO in 1.0 M KOH containing 1.0 M methanol. This current density was about two-fold higher than that of Ni3 Sn2 electrodes (563 mA mg −1 ). The excellent performance obtained with the substitution of small amounts of Ni by Co was concomitant with an increase of the surface coverage of active species and an enhancement of the diffusivity of the reaction limiting species. Additionally, saturation of the catalytic activity at higher methanol concentrations was measured for Ni3− x Co x Sn2 NP-based electrodes containing a small amount of Co when compared with binary Ni3 Sn2 NPs. While the electrode stability was improved with respect to elemental Ni NP-based electrodes, the introduction of small amounts of Co slightly decreased the cycling performance. Additionally, Sn, a key element to improve stability with respect to elemental Ni NPs, was observed to slowly dissolve in the presence of KOH. Density functional theory calculations on metal alloy surfaces showed the incorporation of Co within the Ni3 Sn2 structure to provide more effective sites for CO and CH3 OH adsorption. However, the relatively lower stability could not be related to CO or CH3 OH poisoning.